2018
DOI: 10.1002/cncr.31639
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported fatigue in children with advanced cancer: Results of the PediQUEST study

Abstract: Background Pediatric cancer-related fatigue is prevalent and significantly impairs health-related quality of life, yet its patterns and correlates are poorly understood. We aimed to describe fatigue prospectively reported by children with advanced cancer, and to identify factors associated with fatigue and associated distress. Methods Children (≥2 years) with advanced cancer (N=104) or a parent at three academic hospitals reported their symptoms at most weekly, over nine months, using the computer-based Pedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 46 publications
0
32
0
2
Order By: Relevance
“…Although the broader literature implies that other differences we observed, such as reduced hospital stays and more advance care planning, are indicative of better care, 63 there is no evidence that these changes in the delivery of care reflect family preferences, 48,51,57 or lead to reduced symptom burden, which studies continue to show is significant for children with cancer. 5,90,97 The integration of findings from evaluation studies and those which have explored factors affecting access tells us that while end-of-life care may be different for children who receive specialist palliative care, children who receive this are also different to those who do not, particularly in terms of their disease profile and care processes. Synthesis of the qualitative studies go some way to explaining these differences, highlighting in particular the central role of clinicians' emotions, beliefs and attitudes in shaping referral practices, and the ongoing uncertainty about when to initiate palliative care and whether this should be provided by a specialist service or the oncology team.…”
Section: What This Review Addsmentioning
confidence: 99%
“…Although the broader literature implies that other differences we observed, such as reduced hospital stays and more advance care planning, are indicative of better care, 63 there is no evidence that these changes in the delivery of care reflect family preferences, 48,51,57 or lead to reduced symptom burden, which studies continue to show is significant for children with cancer. 5,90,97 The integration of findings from evaluation studies and those which have explored factors affecting access tells us that while end-of-life care may be different for children who receive specialist palliative care, children who receive this are also different to those who do not, particularly in terms of their disease profile and care processes. Synthesis of the qualitative studies go some way to explaining these differences, highlighting in particular the central role of clinicians' emotions, beliefs and attitudes in shaping referral practices, and the ongoing uncertainty about when to initiate palliative care and whether this should be provided by a specialist service or the oncology team.…”
Section: What This Review Addsmentioning
confidence: 99%
“…The terms advanced/ relapsed/refractory cancer, QOL, and pediatric/child in the title or abstract yielded 38 results, of which 10 evaluated QOL in children with advanced cancer. Most of the publications describe the outcomes of the PediQUEST study (Bilodeau et al, 2019;Ilowite et al, 2018;Rosenberg et al, 2016;Ullrich et al, 2018;Wolfe et al, 2014Wolfe et al, , 2015. This was a multisite, prospective, longitudinal study at three urban, academic medical centers evaluating symptom distress and QOL in children with advanced cancer who were >2 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…This was a multisite, prospective, longitudinal study at three urban, academic medical centers evaluating symptom distress and QOL in children with advanced cancer who were >2 years of age. The central findings of the PediQUEST study were that cancer symptoms, such as pain, sadness, fatigue, vomiting, and anorexia were associated with distress and lower QOL in children with advanced cancer (Rosenberg et al, 2016;Ullrich et al, 2018;Wolfe et al, 2014Wolfe et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the interrelations between fatigue and its co-occurring symptoms provides a new lens for symptom assessment and management. Specifically, recent studies have suggested that a child experiencing a high level of symptom distress is more likely to experience fatigue (Ullrich et al, 2018) and that a single-item fatigue baseline measure could significantly predict symptom profile (fatigue, depression, anxiety, and pain interference) in terms of high or low symptom severity (Wang et al, 2018). The evidence underscores the usefulness of fatigue research findings for clinical applications.…”
Section: Discussionmentioning
confidence: 95%